The Sunan Hadith Collection as a Methodological Instrument: A Novel Study of Its Typology, Quality, and Role in Legal Inference - Muhammad Badrus Sholeh; Ahmad Musyafiq (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2025)
This research examines the strategic role of the Sunan collections in the history of hadith codification, which serve as the second source of Islamic law after the Qur’an. The Sunan works Sunan Abī Dāwūd, Sunan al-Tirmiżī, Sunan al-Nasā’ī, and Sunan Ibn Mājah, were arranged systematically according to chapters of jurisprudence. This structure makes them central references in Islamic law (ahkām), as it facilitates scholars and jurists in locating and interpreting hadiths relevant to legal issues. The study employs a qualitative-descriptive method through library research, using both primary sources such as hadith texts and classical scholarship, as well as secondary sources from modern literature. Findings indicate that each Sunan collection has unique features in selection, classification, and reliability of narrations. Sunan al-Nasā’ī is known for its strict standards, mostly including authentic hadiths, while Sunan Ibn Mājah contains a wider range of reports, including weak and even fabricated narrations. Sunan al-Tirmiżī provides evaluations of hadith status along with scholarly opinions, and Sunan Abī Dāwūd is highly regarded for its authoritative legal narrations. Collectively, the Sunan serve not only as documentation of hadith but also as methodological tools that support verification, classification, and systematic derivation of Islamic law.